Study of Upset Protrusion Joining Process for Joining a Cast Magnesium Component to Other Sheet Materials - Andreae, Nicholas (My University, 2015)
Magnesium alloys are being increasing considered for many automotive applications due their low density and high strength to weight ratio. However, joining of these materials by welding and especially to dissimilar materials such as aluminum or steel or mechanically by riveting at room temperature have faced many challenges. Research presented in thesis explores a new hot joining process referred to as Upset Protrusion Joining (or UPJ) as a means of mechanically joining cast magnesium alloy to other similar or dissimilar sheet materials. UPJ is being developed as a rapid and reliable joining method to be implemented in the automotive industry for weight and manufacturing cost reduction. It involves a cylindrical protrusion emanating perpendicular to the flat surface of a cast plate-like magnesium component that is fitted through a hole in another plate or sheet material. The two components are then clamped together, electrically heated and compressed perpendicular to the axis of the protrusion. During this process, the protrusion expands circumferentially to fill the hole as well as the region above the hole thus entrapping the sheet metal between the mushroomed head and the casting. The effect of different UPJ process parameters such as applied current, current duration, compression loading rate and compression distance were studied through experimentation that involved a newly developed computer-controlled experimental UPJ setup. The studies involved two cast magnesium alloys of interest to automotive industry, AM60 and AZ91, with protrusions of 11 mm diameter and 14 mm height on a 2 mm thick plate. Studies of the material properties and UPJ process parameters were performed to find optimal process parameters to achieve satisfactory quality of the joint in terms of post-UPJ joint strength with appearance. Also, microstructural studies, temperature measurements in the protrusion region, and electrical resistivity measurements were performed for the two alloys to fundamentally understand their roles in promoting temperature dependent material flow, strain localization, and fracture in the UPJ process. Lastly, materials specific process window for UPJ process was identified based on the experimental work for creation of robust UPJ joints with acceptable joint strengths in tensile shear mode of failure. This new hot joining method was shown as an industrially viable joining method for cast magnesium component. UPJ is a rapid joining method and provides good joint-strength depending upon joint specifications. This method can be implemented in automotive and other industrial manufacturing environment for joining cast component to a similar or dissimilar wrought sheet component.
Keywords: Upset Protrusion Joining; Bonding; Magnesium